Burnout and lifestyle of sports coaches in Latvia - Capulis, S.; Dombrovskis, V.; Guseva, S.; Korniševa, A. (LASE Journal of Sport Science, 2020)
Background and Study Aim: The study involves the analysis of the correlation between burnout and lifestyle of sports coaches. Material and Methods:70 sports coaches participated in the study,37 were male and 33 were female. The age of the respondents was between 22 and 62 years (M=42.27; SD=8.81), 34% were aged 36-45, 28% were 26-35, another 28% were 46-55, and 10% were 56-65. The Kern Lifestyle Scale and Maslach Burnout Inventory-Educators Survey were used. Results: The results on each lifestyle scale were determined for the respondents: the highest number of points was found on the Perfection scale -56% of respondents, and the Pleasing scale -27% of respondents. The other scales were characteristic of only 17% of respondents in total. Extremely high overall burnout level was found for 30% of respondents, high results -for 33%, average results -for 26% of respondents, and low burnout results were found for 11% of respondents.The most significant positive correlations were found between the Control lifestyle and Emotional Exhaustion (r=.338; p<.01), as well as Depersonalisation (r=.446; p<.01), and no significant correlation was found between the Pleasing scale and the burnout dimensions. A statistically significant positive correlation was found between the Perfectionism scale and Personal accomplishment (r=.455, p<.01).Conclusions: The results of the study show that lifestyles correlate with professional burnout. Sports coaches who tend to strive for excellent results -high on the Perfection scale and show no deep concern for imperfection, perceive difficulties as a positive challenge, get actively involved in the sports activity and do not develop the burnout syndrome. Coaches with a predominant Expectation lifestyle tend to feel dissatisfied and have a set of unfulfilled expectations regarding themselves or others. If dissatisfaction and unrealistic expectations are not duly satisfied, the specialist may start having a very critical and cynical attitude to themselves and others, which is the core of depersonalisation.